A non-randomised pragmatic trial of a school-based group cognitive-behavioural programme for preventing depression in girls - Heléne Zetterström Dahlqvist; Evelina Landstedt; Ylva B Almqvist; Katja Gillander Gådin (International Journal of Circumpolar Health, 2017)
The aim of this study was to investigate the effectiveness of the DISA-programme in preventing depressive symptoms (DS) in adolescent girls, as implemented in a real-world school setting, accounting for baseline socioeconomic and psychosocial factors, and to investigate whether the effects of these baseline variables on DS differed between intervention participants and non-participants. In this non-randomised pragmatic trial, an electronic questionnaire was disseminated in 2011 (baseline) and 2012 (follow-up) in schools in one municipality in northern Sweden. Pupils (total n=275; intervention participants identified in the questionnaire: n=53; non-participants: n=222) were 14–15 years old at baseline. The groups were compared by means of SEM. DISA could not predict differences in DS at follow-up in this real-life setting. In the overall sample, sexual harassment victimisation (SH) at baseline was associated with DS at follow-up and the estimate for SH increased in the DISA-participants compared to the overall sample.